A 14-years old boy having excessive overjet and traumatic bite (Bangabandhu Sheikh Mujib Medical University Journal, 2019)
This article has no abstract. The first 100 words appear below:A 14-year-old male came to the outpatient Department with the complaints of proclination of the tooth and inability to close his lips. The patient was psychologically depressed for his facial appearance. Extraoral clinical examination showed a mesocephalic symmetrical face with convex facial profile as well as his lower lip was trapped The  nasolabial angle was acute. His mandibular movement was normal and there was no temporomandibular joint dysfunction.